Gis-Based Assessment of Socio-Economic Impacts of Swamp Reclamation in Abonnema, Rivers State, Southern Nigeria - Uzodianya Michael Didia; Stewart S. Owukio (International Journal of Information Systems and Informatics, 2022)
Abonnema in Rivers State is a significant town with a riverine domain in the Kalabari Kingdom in Akuku-Toru Local Government Area, Rivers State, Nigeria is surrounded by water. The town, founded in 1882 and with a population of 74468, is located in the southwest of the State. Because of its overcrowding and the demand for new housing, Abonnema became interested in land reclamation. The aim of this study was to determine the benefits and drawbacks of marsh reclamation on livelihood and infrastructure delivery in Abonnema. The Rivers State Ministry of Works and perspective aided in the provision of data, through field observations, questionnaire surveys, land-sat imagery, and sky-view lifetime drone pictures for this project. To assess the percentage of land cover in the research area, supervised classification of image processing was used. Land reclamation activities have resulted in the destruction and displacement of organisms and species, although most people have benefited from them, according to the findings. The development of infrastructure and access to employment possibilities, the expansion of land capacity, and the improvement of inhabitants' living standards are just a few of the benefits. As a result, the study recommends that the Rivers State Government continue to reclaim more land, particularly in other islands in the state, so that these islands can benefit from infrastructural development, as well as enacting more laws and strategies to regulate reclamation activities across the state. Environmental awareness and perception of the environment should be a component of educational organizations' responsibilities